Measurement of Cortisol and Testosterone in Hair of Obese and Non-Obese Human Subjects - Chan, J.; Sauvé, B.; Tokmakejian, S.; Koren, G.; Van Uum, S. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Objective: Hair analysis has been demonstrated to accurately reflect exposure to drug abuse, environmental toxins and exogenous hormones. We tested the feasibility of measuring cortisol and testosterone in hair of healthy and obese subjects.Measurements: A modified immunoassay (ELISA) originally developed for saliva was used. Hair, urine and blood samples were collected from young non-obese and obese patients. Perceived stress (PSS) was measured using a validated questionnaire.Results: There was no difference in PSS between non-obese and obese subjects. Hair cortisol levels were significantly correlated with weight (r=0.27, p<0.05) and systolic blood pressure (r=0.28, p<0.05), while the correlation with BMI did not reach statistical significance (p=0.063). Hair cortisol levels did not correlate with age or urinary cortisol. There was a negative correlation between hair testosterone and age (r=−0.47, p<0.05) and BMI (r=−0.40, p<0.05). The correlation between hair testosterone and free androgen index (FAI) did not reach statistical significance (p=0.098). The ratio of hair cortisol over hair testosterone (C/T) was higher in the obese group than in the young non-obese group. The C/T ratio correlated positively with age (r=0.56, p<0.01), waist circumference (r=0.63, p<0.01) and BMI (r=0.62, p<0.01), while the correlation between C/T ratio and FAI did not reach statistical significance.Conclusion: Hair cortisol levels increase, while hair testosterone levels decrease with obesity. The hair C/T ratio was significantly correlated with age, BMI and waist circumference better than hair cortisol or testosterone alone. As hair collection is non-invasive and is not influenced by moment-to-moment variations, the measurement of hormones in hair is a useful tool in research and possibly clinical practice.
Keywords: cortisol; testosterone; ratio; hair; obesity